Screening for pediatric abusive head trauma: Are three variables enough?. (March 2022) - Hymel, Kent P.; Karst, Wouter; Marinello, Mark; Herman, Bruce E.; Frazier, Terra N.; Carroll, Christopher L.; Armijo-Garcia, Veronica; Musick, Matthew; Weeks, Kerri; Haney, Suzanne B.; Pashai, Afshin; Wang, Ming; et al.
Abstract: Background: The PediBIRN 4-variable clinical decision rule (CDR) detects abusive head trauma (AHT) with 96% sensitivity in pediatric intensive care (PICU) settings. Preliminary analysis of its performance in Pediatric Emergency Department settings found that elimination of its fourth predictor variable enhanced screening accuracy. Objective: To compare the AHT screening performances of the "PediBIRN-4" CDR vs. the simplified 3-variable CDR in PICU settings. Participants and settings: 973 acutely head-injured children <3 years hospitalized for intensive care across 18 sites between February 2011 and March 2021. Methods: Retrospective, secondary analysis of the combined, prospective PediBIRN data sets. AHT definitional criteria and physicians' diagnoses were applied iteratively to sort patients into abusive vs. other head trauma cohorts. Outcome measures of CDR performance included sensitivity, specificity, predictive values, likelihood ratios, ROC AUC, and the correlation between each CDR's patient-specific estimates of AHT probability and the overall positive yield of patients' completed abuse evaluations. Results: Applied accurately and consistently, both CDR's would have performed with sensitivity ≥93% and negative predictive value ≥91%. Eliminating the PediBIRN-4's fourth predictor variable resulted in significantly higher specificity (↑′d ≥19%), positive predictive value (↑′d ≥8%), and ROC AUC (↑′d ≥5%), but a 3% reduction in sensitivity. Both CDRs provided patient-specific estimates of abuse probability very strongly correlated with the positive yield of patients' completed abuse evaluations (Pearson's r = 0.95 and 0.91, p  = .13). Conclusion: The PediBIRN 3-variable CDR performed with greater AHT screening accuracy than the 4-variable CDR. Both are good predictors of the results of patients' subsequent completed abuse evaluations. Highlights: Two PediBIRN clinical decision rules (CDR) screen effectively for abusive head trauma. The PediBIRN 4-variable clinical decision rule casts a broad net to detect 96% of cases. The PediBIRN 3-variable clinical decision rule detects 93% of cases with fewer false positives. Both CDRs predict the positive yield of patients' subsequent completed abuse evaluations.